Pilot Study on Genetic Associations With Age-Related Sarcopenia - Urzi, Felicita; Pokorny, Boštjan; Buzan, Elena (Frontiers in Genetics, 2021)
Despite strong evidence of an inheritable component of muscle phenotypes, little progress has been made in identifying the specific genetic factors involved in the development of sarcopenia. Even rarer are studies that focus on predicting the risk of sarcopenia based on a genetic risk score. In the present study, we tested the single and combined effect of seven candidate gene variants on the risk of sarcopenia. Single nucleotide polymorphisms in candidate genes were genotyped using the KASP™ assay. We examined 190 older adults that were classified as nonsarcopenic or sarcopenic according to the diagnostic criteria of the European Working Group on Sarcopenia in Older People. Sarcopenia was associated with Methylenetetrahydrofolate reductase, Alpha-actinin-3, and Nuclear respiratory factor 2 genotypes. The combined effect of all three polymorphisms explained 39% of the interindividual variation in sarcopenia risk. Our results suggest that the single and combined effect of Methylenetetrahydrofolate reductase, Alpha-actinin-3, and Nuclear respiratory factor 2 polymorphism is associated with sarcopenia risk in older adults. Nowadays, as the population is getting older and older, great efforts are being made to research the etiology, diagnosis and treatment of sarcopenia. At the same time, small progress has been made in understanding the genetic etiology of sarcopenia. Given the importance of research on this disease, further genetic studies are needed to better understand the genetic risk underlying sarcopenia. We believe that this small-scale study will help to demonstrate that there is still much to be discovered in this field.